2023
DOI: 10.1177/00405175231206554
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the support panel of compression leggings on the provision of low pressure for foot progression angle correction

Hye Suk Kim

Abstract: This study developed compression leggings (CLs) with a support panel for foot progression angle (FPA) correction to improve the fit without restricting the user's movement while providing an appropriate external force. This study aimed to examine the effects of FPA correction concerning the functionality and usability of the support panel of CLs that ensure low pressure. Clothing pressure (CP), FPA, skin blood flow (SBF), perceived strength, and usability of OCLs during treadmill walking were compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Furthermore, the higher-pressure gradient provided by GCLs exhibited a superior FPA correction effect compared with FCLs. A previous study 11 demonstrated that the support panel, as a design factor, has a corrective effect on FPA in healthy individuals. As a subsequent study, the current study identifies AP for generating graduated pressure, which serves as a controlling variable for corrective function.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, the higher-pressure gradient provided by GCLs exhibited a superior FPA correction effect compared with FCLs. A previous study 11 demonstrated that the support panel, as a design factor, has a corrective effect on FPA in healthy individuals. As a subsequent study, the current study identifies AP for generating graduated pressure, which serves as a controlling variable for corrective function.…”
Section: Resultsmentioning
confidence: 97%
“…Subsequently, a modified support panel derived from the initial prototype 11 was embedded into the ground pattern. The principle of the support panel proposed by Kim 11 was to mitigate the contraction of muscles and fascia during locomotion, thereby internally rotating the hip joint through a technique of restricting muscle movement by adjusting the tension of elastic materials [39][40][41][42][43] (KR patent no.…”
Section: Test Conditionsmentioning
confidence: 99%
See 3 more Smart Citations